Perancangan Tempat Tidur Bayi Dan Lemari Multifungsi Yang Ergonomis Dengan Menggunakan Produk Recycle Drum - Agus Topo Subekti; Asfia Fitri Aras (Jurnal INOVATOR, 2019)
Cribs are one of the baby support products used after the baby is born. Parents as consumers expect products that are used more concise, in accordance with the residence and the price is more economical by not reducing the quality of products and still refers to the principle of ergonomics, so that the product is less competitive with existing products in the market therefore it is necessary to design ababy crib and ergonomic multifunction cabinets by using the productrecycle drum. The purpose of this design is expected to answer and be a solution to the wishes of consumers, especially parents who have a baby by presenting new innovations. The design uses anthropometry theory to produce a convenient product used by the user. Anthropometric data collection is done directly with the required body dimensions are height upright, shoulder width and hand reach. Stages of data processing ie test data adequacy, test data uniformity and percentile calculations. The Results of design of ergonomic crib and cupboardare made based on the anthropometry of the human body, as well as economical because it is made using recycled materials....